2020
DOI: 10.1371/journal.pone.0234994
|View full text |Cite
|
Sign up to set email alerts
|

Plastic response of the oyster Ostrea chilensis to temperature and pCO2 within the present natural range of variability

Abstract: Estuaries are characterized by high fluctuation of their environmental conditions. Environmental parameters measured show that the seawater properties of the Quempillé n estuary (i.e. temperature, salinity, pCO 2 , pH and ΩCaCO 3) were highly fluctuating and related with season and tide. We test the effects of increasing temperature and pCO 2 in the seawater on the physiological energetics of the bivalve Ostrea chilensis. Juvenile oysters were exposed to an orthogonal combination of three temperatures (10, 15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…Curiously, despite size differences associated with parental treatments in the Oyster Bay population, there were no differences in gene expression. Differing sizes may therefore not be due to variable growth rate, as that would likely have been reflected in expression profiles (Meyer & Manahan, 2010; Pace et al, 2006). It is possible that cryptic intergenerational transcriptome plasticity could be induced by high pCO 2 or other environmental stressors, but that was not revealed under ambient conditions in which larvae were reared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curiously, despite size differences associated with parental treatments in the Oyster Bay population, there were no differences in gene expression. Differing sizes may therefore not be due to variable growth rate, as that would likely have been reflected in expression profiles (Meyer & Manahan, 2010; Pace et al, 2006). It is possible that cryptic intergenerational transcriptome plasticity could be induced by high pCO 2 or other environmental stressors, but that was not revealed under ambient conditions in which larvae were reared.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported little to no effects of acidification in Ostrea spp. at the adult (Lemasson et al, 2018;Lemasson et al, 2019;Lemasson & Knights, 2021), juvenile (Navarro et al, 2020), and larval stages (Cole et al, 2016;Pereira et al, 2019;Waldbusser et al, 2016). In one study O. edulis larval growth and survival responded positively to acidification exposure (Prado et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Warming seawater and air temperature in combination with decreasing alkalinity will increase the maintenance costs of intertidal populations. The impact of these factors and synergistic effects on the performance of the Ostrea and the Crassostrea genus have recently been a focus of study and concluded that larvae from brooding species were more tolerant to ocean acidification (in combination with other pressures) compared with broadcaster species ( Gazeau et al, 2013 ; Ko et al, 2014 ; Cole et al, 2016 ; Gray et al, 2019 ; Navarro et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the northern quahog, Mercenaria mercenaria, the combined effects of warming and increased CO 2 resulted in increased RR, but no effect was observed in the Eastern oyster, Crassostrea virginica [28]. Conversely, the oyster Ostrea chilensis showed no effects of high temperature and CO 2 upon physiological processes, indicating that this species may show high tolerance to these changes [29]. The above findings demonstrate that CO 2 and warming should be studied concomitantly as the interaction of these two factors may change the response of a species to future environmental conditions.…”
Section: Introductionmentioning
confidence: 94%